Survey of Obstacles to Online Learning for Physics Subjects in Middle Schools During the Covid-19 Pandemic Period in Palu City - Hijriah; Saehana, Sahrul (Universitas Tadulako, 2023)
This study aims to determine the obstacles to online learning of physics subjects in secondary schools during the COVID-19 pandemic in Palu City. This type of research is descriptive quantitative research with survey methods using data collection techniques in the form of questionnaires. The questionnaire was made online through a Google Form containing 24 statements to 368 respondents. The results of this study indicate that the biggest obstacles experienced by students during online learning of physics subjects are indicators of student motivation and interest, student participation, and economic constraints.